So super-starry - Wilkins, Rose. (London : Macmillan Children's Books, 2004)
Fifteen-year-old Octavia Clairbrook-Cleeve, the daughter of a famous television actress and a respected film and theater director, feels out of place amidst the glamour, wealth, and high society that surround her, and when she begins dating a rich and handsome older boy, her doubts about this lifestyle become impossible to ignore.
Keywords: Divorce -- Fiction; Fame -- Fiction; Identity -- Fiction; Interpersonal relations -- Fiction; Schools -- Fiction; England -- Fiction; London (England) -- Fiction